Fuzzy Signature Based Organization of Material Handling in Functional Production Systems - Ferenczi, Balázs; Lilik, Ferenc (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2021)
The efficient management of material handling in a functional production system is just as complex as production scheduling. The costs of production losses are affected by the expertise and the decisions of the operative logistics personnel. Automation is one possible way of increasing the efficiency and decreasing the losses derived from poor human decisions. Although the total automation of material handling using robots and automated guided vehicles is technically possible, it is difficult to realize due to high standardization requirements. To improve efficiency, the replacement of human decisions with computer decisions is a feasible solution for existing companies, however, the exact mathematical modeling of such complex systems may be difficult since special knowledge and expertise is needed. The aim of the article is to present an easier computerized method by modeling human decisions of local experts using fuzzy logic. The fuzzy signature-based method is proposed, based on the operating practices of a real production plant. The experimental results compared with the mathematical optima given by linear programming are presented. The proposed optimization method is more simple than already existing ones, therefore it can be suitable for small and medium-sized companies.